The White Man’s Burden? How to Come to Terms With Whiteness as Identity Category (KULT_online, 2016)
In White Self-Criticality beyond Anti-Racism George Yancy, scholar of the philosophy of race, further develops his insights into the nature of being white, and hence being a white problem for all those not sharing this privileged identity category. By assembling fourteen white scholars in the field of critical whiteness studies, this volume provides a critical perspective on the unfinished project of and ongoing personal struggles with forging an anti-racist white identity. Furthermore, this essay collection delineates thought-provoking analytical approaches to dismantling white privilege in the academy and beyond.